Закономерности формирования элементного состава кальций-фосфатных покрытий со временем микродугового оксидирования - Акимова, Елизавета Борисовна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
It was found that an increase in the MAO process duration from 2 to 10 min led to a change in the elemental composition of calcium phosphate coatings: the calcium concentration increased in the range of 3.2 – 5.5 at.%, the titanium amount decreased in the range of 13.6 – 8.9 at.%, the phosphorus and oxygen amounts remained constant in the ranges of 15.4 – 16.2 at.% and 67.1 – 69.7 at.%, respectively.